Losing compassion for patients? The implications of COVID-19 on compassion fatigue and event-related post-traumatic stress disorder in nurses. Issue 3 (24th January 2022) - Hochwarter, Wayne; Jordan, Samantha; Kiewitz, Christian; Liborius, Patrick; Lampaki, Antonia; Franczak, Jennifer; Deng, Yufan; Babalola, Mayowa T.; Khan, Abdul Karim
Abstract : Purpose: The authors investigated a psychological process that links characteristics of events related to the coronavirus disease (2019) COVID-19 pandemic (i.e. perceived novelty, disruptiveness and criticality) to compassion fatigue [(CF), a form of caregiver burnout] and subsequent post-traumatic stress disorder (PTSD) in nurses. Design/methodology/approach: Administering two online surveys (October and November 2020) resulted in matched data from 175 nurses responsible for patient care during the COVID-19 pandemic. Findings: Perceived disruptiveness and criticality of COVID-19 events were positively associated with nurses' CF, which also mediated those characteristics' effects on PTSD instigated by COVID-19. Contrary to the authors' hypothesis, the perceived novelty of COVID-19 events was not significantly associated with CF nor was the indirect effect of perceived novelty on PTSD mediated by CF. Originality/value: The authors extend event system theory by investigating the psychological processes linking event features and resultant outcomes while providing practical implications on preparations for future unexpected and potentially life-altering events.